Implementasi Kurikulum Merdeka Dan Dampaknya Terhadap Pelayanan Pendidikan Di Persekolahan Setia Pontianak - Gihon Nenabu (JURNAL LUXNOS, 2025)
This article discusses the implementation of the Merdeka Curriculum and its impact on educational services at the Setia Pontianak School. The Independent Curriculum is an educational policy that emphasizes learning that is flexible, student-centered, and contextual according to local needs. This research uses a qualitative descriptive approach with data collection techniques through observation, interviews and documentation studies. The results of the analysis show that the implementation of the Merdeka Curriculum at Setia School has encouraged a significant transformation in learning practices, including the use of a differentiation approach, problem-based projects, and strengthening formative assessments. In addition, increasing teacher capacity and strengthening collaboration between stakeholders also supports the creation of an inclusive and responsive learning environment. Even though there are challenges such as limited resources and educator readiness, overall the Merdeka Curriculum makes a positive contribution to improving the quality of educational services. These findings indicate the need for ongoing assistance and evaluation so that curriculum implementation can run optimally and sustainably.